2020
DOI: 10.36941/jesr-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors for Performance Oriented M-Learning in Sri Lanka

Abstract: Students engaged with multi tasks commitments demand modern learning environments facilitated with virtual engagements and high-tech contact methods. Thus, they are looking for such technically equipped learning facilities avoiding physical presence where they can learn at anytime and anywhere. The mobile devices provide many facilities for education sector providing execution supports for M-learning. This has reshaped the education model of many countries and institutions. Sri Lanka is an emerging economy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In this study, the author has identified six broad factors namely mechanics & aesthetics, self-benefits, social interaction, and selfachievement. The usage of mobile commerce would also be an avenue to penetrate the gamification as a business opportunity by providing easy access opportunities for clients as per some studies highlight the advancements of mobile commerce in general (Dissanayake & Velananda, 2020). Accordingly, it is noticed that gamification has grown in significance in mobile e-commerce platforms as a means of enticing users and promoting subsequent visits.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the author has identified six broad factors namely mechanics & aesthetics, self-benefits, social interaction, and selfachievement. The usage of mobile commerce would also be an avenue to penetrate the gamification as a business opportunity by providing easy access opportunities for clients as per some studies highlight the advancements of mobile commerce in general (Dissanayake & Velananda, 2020). Accordingly, it is noticed that gamification has grown in significance in mobile e-commerce platforms as a means of enticing users and promoting subsequent visits.…”
Section: Discussionmentioning
confidence: 99%
“…Ease of use in learning with AI refers to the ability to master AI with less effort. The easier the tools students use, the greater the benefits and uses (Dissanayake & Velananda, 2020;Stylios et al, 2022;Suki & Suki, 2017). So that it allows students to use technology in every learning process (Abdullah et al, 2016;Maheshwari, 2021).…”
Section: Perceived Usefulness (Puai)mentioning
confidence: 99%